From Meaningful Learning to Behavioral Change: The Implementation of Deep Learning in Religious Ethics to Prevent Student Delinquency - Rudi Hamsyah; Abdurrahmansyah Abdurrahmansyah; Muhammad Abdillah Asmara (PT. Pusmedia Group Indonesia, 2026)
The Deep Learning approach is one of the educational innovations developed to foster meaningful, reflective, and transformative learning. In the context of Islamic Religious Education, Akidah Akhlak instruction is not only intended to enhance students’ conceptual understanding but also to shape character and foster positive behavioral change. This study aims to analyze the implementation of the Deep Learning approach in Akidah Akhlak instruction and its contribution to preventing student delinquency in madrasahs. The study employed a qualitative approach using a case study method at MTs Negeri 1 Musi Banyuasin from November 2025 to April 2026. Research informants included the madrasah principal, Akidah Akhlak teachers, the vice principal for student affairs, guidance counselors, and students selected using purposive sampling. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of Deep Learning in Akidah Akhlak instruction is carried out through contextual learning, reflection on experiences, critical discussion, collaborative learning, and authentic assessment, which encourage students to understand and internalize Islamic values in their daily lives. This meaningful learning process contributes to strengthening moral awareness, self-control, social responsibility, and reducing tendencies toward delinquent behavior such as violations of school rules, bullying, and undisciplined behavior. The research findings produced a conceptual model of behavioral change indicating that meaningful learning through Deep Learning fosters the internalization of values, character development, and behavioral transformation among students. The contribution of this research lies in the development of a Deep Learning perspective in Islamic Education that is not only oriented toward academic achievement but also toward behavioral change and the prevention of student delinquency as part of the goals of character education in the era of educational transformation.